Production of Agaricus bisporus in Zaccar (Algeria) - Hassina, Guetarni; Meriem, Sadahine; Samira, Bengoufa (Mushroom Research, 2021)
Mushroom production is very well suited to sustainable agriculture. Mushrooms provide additional protein, essential vitamins and minerals. The objective of the work is to promote mushroom culture through cultivation of white button mushroom (Agaricus bisporus) mycelium. The product obtained at the end of this operation is called “white mother” which will be used later to inoculate the fruiting substrate based on horse manure and straw. From the kits, pure cultures of mycelium were prepared on Potato dextrose agar medium, which were then inoculated into various sowing substrates under strict aseptic conditions. The results show that the cultivated fungus is sensitive to various fungal pathogens.